The potential impact of climate change environmental hazards on quality of life of fishermen community in Malaysia - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; Uli, Jegak; D’Silva, Jeffrey Lawrence (American-Eurasian Network for Scientific Information, 2011)
Climate change is not a new phenomena and has already bring concerns to us. A lot of community groups have suffered from the impacts of the climate change. Farmers, businessmen, tourists, older people and children are going to be challenged like never before as climate change exerts a multi-faceted influence. Other than these groups, what about the fishermen? Are their social, economic and health aspects are going to be affected by the impacts of climate change? The answer of this question will fulfill the main objective of this paper which is to discover the climate change impact on the fishermens quality of life. This is a qualitative study where the data was gained through literature analysis and document analysis. Based on the analysis done, it can be concluded that the climate change will obstruct fishermen from doing their routine tasks, bring damages to their belongings, reduce the quantity and quality of the sea faunas which will affect their productivity and expose them to diseases related to malaria, skin problems, fever, flu, cough and other health problems. It is recommended that the fishermen in Malaysia must be socially and economically prepared so that they can face the impacts brought by the climate change.